2011
DOI: 10.1002/hipo.20815
|View full text |Cite
|
Sign up to set email alerts
|

Dentate gyrus granule cell firing patterns can induce mossy fiber long‐term potentiation in vitro

Abstract: Hippocampal granule cells transmit information about behaviourally-relevant stimuli to CA3 pyramidal cells via mossy fiber synapses. These synapses express a form of long-term potentiation (mfLTP) that is non-Hebbian and does not require NMDA receptors. mfLTP is thought to be induced and expressed presynaptically, hence, the major determinant of whether mfLTP occurs is activity in the granule cells. However, it remains unclear whether mfLTP can be induced by activity patterns that granule cells exhibit in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 39 publications
(62 reference statements)
1
37
0
Order By: Relevance
“…Stimulation-induced synaptic discharges led to somatic depolarization that was sufficient for the cell to fire, and we varied the stimulus strength from trial to trial so that the rise time of somatic depolarization before the first AP ranged from 5–8 to 100–200 ms. This type of granule cell activity is well within the range documented in behaving animals30. We found that in every tested cell, the spiking threshold increased robustly when the depolarization rate was slowed down (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Stimulation-induced synaptic discharges led to somatic depolarization that was sufficient for the cell to fire, and we varied the stimulus strength from trial to trial so that the rise time of somatic depolarization before the first AP ranged from 5–8 to 100–200 ms. This type of granule cell activity is well within the range documented in behaving animals30. We found that in every tested cell, the spiking threshold increased robustly when the depolarization rate was slowed down (Fig.…”
Section: Resultssupporting
confidence: 84%
“…[16]. Following a post-slicing recovery period of > 1 hr slices were transferred to an interface-type recording chamber constantly perfused with artificial cerebrospinal fluid (aCSF) at 33°C.…”
Section: Methodsmentioning
confidence: 99%
“…It is perhaps surprising that so few granule cells discharge during normal behavior (Alme et al, 2010) and at such low firing frequencies (<0.2 Hz; Jung and McNaughton, 1993). More recent studies, however, report that higher spike frequencies (averaging about 1 Hz) normally occur (Leutgeb et al, 2007; Mistry et al, 2011). Moreover, during behavioral tasks, many perforant path axons conduct impulses at rates of 10–20 Hz or more (Fyhn et al, 2007), while granule cells may generate high frequency bursts of impulses (Mistry et al, 2011).…”
Section: Implications Of the Lamellar Hypothesis For Understanding Dementioning
confidence: 98%